A Novel Ultrasound-Based Carotid Plaque Risk Index Associated with the Presence of Cerebrovascular Symptoms - Kanber, B.; Hartshorne, T. C.; Horsfield, M. A.; Naylor, A. R.; Robinson, T. G.; Ramnarine, K. V. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: The purpose of this study was to determine the efficacy of a novel ultrasound-based carotid plaque risk index (CPRI) in predicting the presence of cerebrovascular symptoms in patients with carotid artery stenosis.Materials and Methods: This was a cross-sectional, observational study involving 56 patients (mean age 76.6 years, 62.5 % male). Plaque grayscale median (GSM) and surface irregularity indices (SII) were measured in 82 stenosed carotid arteries (range 10 – 95 %) and combined with the degree of stenosis (DOS) in the form of (DOS*SII)/(1 + GSM). A reduced index DOS/(1 + GSM) not incorporating plaque surface irregularities was also investigated. Receiver operating characteristic curves (ROC) were used to study the diagnostic efficacy of CPRI, comparing against DOS and an equivalent risk index constructed using a conventional logistic regression based method with model parameters optimized to the dataset (CPRIlogistic).Results: There were 42 stenosed carotid arteries with cerebrovascular symptoms, and 40 without symptoms. The presence of symptoms significantly correlated with DOS, GSM and SII (p < 0.01). The median CPRI of the symptomatic (asymptomatic) groups were 23.2 (9.2) compared with 0.71 (0.30) for CPRIlogistic (p < 0.01). The diagnostic performance of CPRI exceeded that of CPRIlogistic and DOS, and demonstrated a better separation of the symptomatic and asymptomatic groups.Conclusion: Our novel risk index combines quantitative measures of carotid plaque echogenicity and surface irregularities with the degree of stenosis. It is a better predictor of cerebrovascular symptoms than the degree of stenosis and could be valuable in studies and clinical trials aimed at identifying vulnerable carotid artery stenoses.
Keywords: carotid plaque; risk index; CPRI